Evaluating the students' level of cognitive engagement to achieve english language curriculum objectives at International Islamic School, Gombak - sani, Abu Bakar; Hashim, Che Noraini (SCIENCEDOMAIN international, 2016)
This study evaluates the level of cognitive engagement in English class among secondary school students of International Islamic School in Gombak, Malaysia. Specifically, the objective of this research is to appraise the students' commitments in English class by observing their level of cognitive engagement, which can be deep or shallow; and this is done considering their gender, age and grades. The school has five grades (7-11) and the research was conducted in January 2014. It involves 191 participants (male and female) by using purposive sampling, ages range between 13 to 18 years. Data were obtained through questionnaire, which contains a 5-point Likerts scale.However, descriptive statistics was used to describe the level of cognitive engagement employed by the students in English language class. Thus, the overall results show that deep engagement is more associated with male students while shallow engagement is associated with their female counterparts. In terms of age, the result reveals those students of the ages 13, 14, 15, and 18,display deep engagement than their colleagues aged 12, 16 and 17. Similarly, concerning grade, students in grade 9 and 10, display deep engagement; whereas those in grade 7, 8, and 11 display shallow engagement in English language class. Therefore, it is recommended that, English teachers should employ all possible efforts in teaching and organizing activities that would enhance females’ attitudes towards deep engagement.